THE RELATIONSHIP BETWEEN PARENTING STYLES AND THE RESILIENCE OF PARENTS WITH CHILDREN WHO HAVE SPEECH DELAYS - Hayya, Wardatul; Suwarjo, Suwarjo (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study is motivated by the increasing incidence of speech delay in early childhood, which not only affects children’s language development but also creates emotional and psychological pressure on parents, making resilience an essential aspect of the caregiving process. This study is significant because parenting patterns are presumed to play a major role in shaping parental resilience when facing developmental challenges in their children. The aim of this research is to analyze the relationship between parenting patterns and the resilience of parents who have children with speech delay. Using a quantitative approach with a correlational design, the study was conducted with 16 parents of children aged 5–6 years at TK Pertiwi 1 Padang, selected through purposive sampling. Data were collected using validated and reliable questionnaires on parenting patterns and parental resilience, and later analyzed through normality tests, linearity tests, Pearson correlation, and simple linear regression. The results indicate that the data were normally distributed and the relationship between variables was linear, with a Pearson correlation coefficient of 0,423 and a significance value of 0,003, indicating a positive, moderate, and significant relationship between parenting patterns and parental resilience. These findings show that warm, responsive, and consistent parenting contributes to parents’ ability to manage stress, maintain emotional stability, and adapt while raising children with speech delay. The study’s implications highlight the importance of family interventions, parenting training, and social support to strengthen parental resilience. The study concludes that parenting patterns are an important factor to consider in efforts to enhance the psychological resilience of families with children experiencing speech delay